Arahan Kawasan Tanggap Bencana Likuifaksi Kota Palu - Rahmatullah Hasan; Abdul Rachman Rasyid; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
One of the impact caused by the earthquake is the phenomenon of loss of the strength of the soil layer due to the earthquake shake that is commonly called liquefaction. A few months ago, a large-scale earthquake occured that caused liquefaction in the city of Palu, especially in Balaroa and Petobo areas. Beside the casualties, the impact of the earthquake was the destruction of settlements, facilities and various infrastructure. Therefore, it is important to identify the liquefaction disaster response cultivation area of Palu City. The purpose of this research are, 1). To identify the pattern of liquefaction movement in Palu city, (2) to identify the suitability of deesignation areas to the pattern of liquefaction movements in Palu City, and (3) to identify the direction of development of liquefaction mitigation zone in Palu City.This research that was conducted in the city of Palu. Data collection was conducted through field surveys (interviews and documentation), literature studies, and institutional visits. The analysis technique used was spatial analysis with the overlay method and scoring. Liquefaction that occurred in Palu City moved in two different directions. But the direction of the movement follows the topography of the Palu City, which is from the highlands to the lowlands. The results of the liquefaction vulnerability analysis show that each sub-district in Palu City has a vulnerable area of ​​liquefaction. Areas susceptible to liquefaction are directed to be developed as designated areas for green open space (RTH), nature reserves and cultural reserves, and tourism.